THE EFFECT OF INTERACTIVE POWERPOINT (PPT) WITH THE ICEBERG APPROACH ON UNDERSTANDING MATHEMATICAL CONCEPTS IN THE TOPIC OF SURFACE AREA OF A CYLINDER - Nadya Ramadhani; Nur Hidayah Br Karo, Hamidah Nasution (Adisam Publisher, 2025)
This study aims to analyze the effect of using interactive PowerPoint (PPT) with the Iceberg approach on students' understanding of mathematical concepts, specifically in the area of cylinder surface area. Students' difficulties in comprehending abstract geometrical concepts necessitate a more effective learning approach. The research employed a quasi-experimental design with pre-test and post-test on two groups: an experimental group using interactive PPT with the Iceberg approach, and a control group using conventional teaching methods. The sample consisted of 60 eighth-grade junior high school students. Results showed a significant improvement in concept understanding for the experimental group compared to the control group, with normalized gain values of 0.78 and 0.37, respectively. T-test analysis revealed a significant difference between the two groups (t = 5.05, p < 0.05). A student perception questionnaire indicated that 83% of students found learning more engaging with interactive PPT. In conclusion, the use of interactive PowerPoint with the Iceberg approach effectively enhances students' understanding of mathematical concepts related to cylinder surface area and increases their learning motivation.